Implementasi Pilar-Pilar Pendidikan UNESCO - Cindy Priscilla; Deddy Yusuf Yudhyarta (STAI Auliaurrasyidin Tembilahan, 2021)
This study aimed to determine the implementation of UNESCO's educational pillars as well as to find out its inhibiting factors at State Vocational High School 1 Tembilahan. This study was a qualitative descriptive study, the proportionate stratified random sampling toward 90 selected students used to gather the data through questionnaires, interviews, and documentation. The result showed that the percentage of the implementation was at 66.37% (Good). Meanwhile, the inhibiting factors in the implementation were the differentiation of students and limited time allocation.